2020
DOI: 10.21203/rs.3.rs-69373/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of MEFV gene in COVID 19 disease, as a protective factor

Abstract: Background In early 2020, an outbreak of pneumonia caused by a novel coronavirus became pandemic. This study evaluates the potential immune-genetically role of MEFV gene mutations in COVID 19 patients. Methods 50 COVID 19 PCR positive patients who were hospitalized in COVID 19 referral centers between 1st of March to 30th of April in 2020 were evaluated for MEFV gene mutations using ARMS PCR and Sanger sequencing. Results MEFV gene mutations were found in 6 (12%) of the patients. No homozygote or compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[49] According to previous studies, the prevalence of MEFV mutations in this region was 25 percent. [49] In the light of the information given, it can be observed that MEFV mutation carriers are at a significantly lower incidence in COVID-19 patients compared to the normal population distribution in the region. [49] In addition, populations of the eastern Mediterranean regions with a high carrier rate of MEFV mutations have a slightly lower prevalence of COVID-19.…”
Section: The Mediterranean Fever (Mefv) Genementioning
confidence: 88%
See 4 more Smart Citations
“…[49] According to previous studies, the prevalence of MEFV mutations in this region was 25 percent. [49] In the light of the information given, it can be observed that MEFV mutation carriers are at a significantly lower incidence in COVID-19 patients compared to the normal population distribution in the region. [49] In addition, populations of the eastern Mediterranean regions with a high carrier rate of MEFV mutations have a slightly lower prevalence of COVID-19.…”
Section: The Mediterranean Fever (Mefv) Genementioning
confidence: 88%
“…[51] In addition, the role of MEFV mutations in COVID-19 disease was investigated in 50 COVID-19 patients diagnosed with PCR test. [49] As a result of the analysis of MEFV gene mutations using Sanger sequencing in these patients, it was found that 6 patients (12%) had heterozygous MEFV mutations. [49] According to previous studies, the prevalence of MEFV mutations in this region was 25 percent.…”
Section: The Mediterranean Fever (Mefv) Genementioning
confidence: 94%
See 3 more Smart Citations